Awareness and Practices of Non-Pharmacological Approaches for Management of Hypertension in a Geriatric Population - Debalina Sahoo; Harshida Gosai; Ujjwal Sahoo; J. M. Harsoda (University Library System, University of Pittsburgh, 2014)
Background: There is an increase in the prevalence of hypertension all over the world, including India. Hypertension can be initially managed with non-pharmacological measures. This study aims to assess the knowledge of non-pharmacological measures to control hypertension and its application in a geriatric hypertensive population. Methods: The study was conducted at the Department of Physiology, SVU, Vadodara, India. A total 110 hypertensive patients were included in the study and a non-validated survey was conducted to examine knowledge of non-pharmacological measures to control hypertension in this group of patients. Frequencies, percentages, means and standard deviations were calculated and reported. Results: Only 10% of the respondents knew the normal values for blood pressure. Approximately 38% of the subjects did not measure their blood pressure regularly. A total of 24% subjects knew that body weight has a correlation with hypertension. About 27% said that there was no correlation between salt intake and hypertension, and 88% of the study population did not carry out any form of physical activity. Conclusion: Hypertension can be controlled by life style modifications such as exercise, weight management and a healthy diet. Public health and education measures targeting hypertensive population need to be taken to decrease the risk factors for cardiovascular diseases and, therefore, improve people's health and quality of life.